Managerial Attitutes Toward Industrial Relations : Public and Private Sectors - Thompson, Mark; Moore, Larry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
The authors analyse possible differences in managerial attitudes toward unionism and collective bargaining in the public and private sectors in Canada. Distinct patterns of attitudes emerge showing more favorable views in the public se et or.